Enhancing quality of student teachers’ practices through reflective journal writing during school practice - Ezati, Betty Akullu; Ocheng, Mary K.; Ssentamu, Proscovia N.; Sikoyo, Leah N. (Faculty of Education, University of the Free State, 2010)
This paper explores the role of journal writing in enhancing student teachers’ learning during school practice. It analyses data from 22 student teachers’ journals and 23 questionnaires. The study focuses on the areas that student teachers reflected on most, the nature of their reflection and the extent to which previous experiences informed their subsequent reflection and learning. Findings showed that student teachers frequently reflected on handling indiscipline issues, procedures and outcomes of supervision, but less on their own learning. Inadequate reflection on their learning suggests that journal writing has not yet sufficiently promoted student teachers’ professional growth. Generally, the examination and cultural orientation in the Ugandan society influence student teachers’ journal writing. Finally, the paper proposes strategies for improving journal writing in order to enhance the potential of students learning from reflection during school practice.
Keywords: Reflective practice; Professional growth; Journal writing; School practice; Uganda